Synthesis and spectral studies of 3,5-bis(4-chlorophenyl)-1-propyl-1,3,5-triazinane - Souhila, Malki; Lefrada, Leila; Bouchemma, Ahcene; Bouhenguel, Mustapha; Chebbah, Mahmoud; Sid, Assia (European Journal of Chemistry, 2016)
A hexahydrotriazine derivative was synthesized via a condensation reaction of 4-chloroaniline, propylamine and formalin. The structure of the synthesized compound was confirmed and characterized by using various spectral techniques like FT-IR, 1H NMR, 13C NMR and UV spectroscopy.